The Effect of Application Positive Affirmation Therapy on Experienced Students of Fatherless - Marpatmawati, Idhfi; Fannia Rahmasari Nurfuadi; Betty Suprapti; Wawan Rismawan; Nandita milda hidayat (HealthCare Nursing Journal, 2025)
The phenomenon of fatherlessness has become a global issue that affects the psychological and emotional development of children into adulthood. This study aims to evaluate the effectiveness of positive affirmation therapy in reducing aggression behavior in female college students who experience fatherlessness. This study used a descriptive qualitative method with the subjects of three female college students aged 20-21 years. Data were collected through a fatherless impact questionnaire, observation sheets, and the implementation of positive affirmation therapy for four intervention sessions. The results showed that the experience of being fatherless had an impact on low self-esteem, lack of security, and inability to establish a close relationship with the father. Positive affirmation therapy significantly decreased aggression scores in all subjects, from severe and moderate categories to moderate. The intervention also improved subjects self-control, as supported by previous research. In conclusion, positive affirmation therapy is effective in addressing the psychological impact of father absence and can be used as a non-pharmacological intervention that supports emotional well-being. Further research is recommended to expand the number of subjects and explore additional interventions.